Overview of Community-Acquired Pneumonia and the Role of Inflammatory Mechanisms in the Immunopathogenesis of Severe Pneumococcal Disease - Helen C. Steel; Riana Cockeran; Ronald Anderson; Charles Feldman (Hindawi Limited, 2013)
Community-acquired pneumonia (CAP) remains a leading cause of morbidity and mortality among the infectious diseases. Despite the implementation of national pneumococcal polyvalent vaccine-based immunisation strategies targeted at high-risk groups, Streptococcus pneumoniae (the pneumococcus) remains the most common cause of CAP. Notwithstanding the HIV pandemic, major challenges confronting the control of CAP include the range of bacterial and viral pathogens causing this condition, the ever-increasing problem of antibiotic resistance worldwide, and increased vulnerability associated with steadily aging populations in developed countries. These and other risk factors, as well as diagnostic strategies, are covered in the first section of this review. Thereafter, the review is focused on the pneumococcus, specifically the major virulence factors of this microbial pathogen and their role in triggering overexuberant inflammatory responses which contribute to the immunopathogenesis of invasive disease. The final section of the review is devoted to a consideration of pharmacological, anti-inflammatory strategies with adjunctive potential in the antimicrobial chemotherapy of CAP. This is focused on macrolides, corticosteroids, and statins with respect to their modes of anti-inflammatory action, current status, and limitations.